The Inventory Growth Spread - Belo, Frederico; Lin, Xiaoji (Review of Financial Studies, 2012)
Previous studies show that firms with low inventory growth outperform firms with high inventory growth in the cross-section of publicly traded firms. In addition, inventory investment is volatile and procyclical, and inventory-to-sales is persistent and countercyclical. We embed an inventory holding motive into the investment-based asset pricing framework by modeling inventory as a factor of production with convex and nonconvex adjustment costs. The augmented model simultaneously matches the large inventory growth spread in the data, as well as the time-series properties of the firm-level capital investment, inventory investment, and inventory-to-sales. Our conditional single-factor model also implies that traditional unconditional factor models such as the CAPM should fail to explain the inventory growth spread, although not with the same large pricing errors observed in the data. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.